2012
DOI: 10.1149/2.082207jes
|View full text |Cite
|
Sign up to set email alerts
|

Composition Gradients and Magnetic Properties of 5–100 nm Thin CoNiFe Films Obtained by Electrodeposition

Abstract: The composition gradient and properties of magnetic 5-100 nm thin CoNiFe films electrodeposited on Cu or Pt substrate were studied. It was found that the average elemental composition of CoNiFe, obtained by ICP analysis, changes during electrodeposition. The extent of anomalous co-deposition achieved at deposit thickness <100 nm was found to be several times larger than in thicker CoNiFe films. The partial current densities for all three metals (Co, Ni, Fe) increase during the time of electrodeposition and giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…In this study, it was revealed that the use of ITO as the substrate led to the formation of amorphous phase, which agreed well with the findings of other workers [36,37]. However, the use of copper substrate for example, can yield crystalline phase of the deposits [38,39]. The amorphous phase is suitable for super capacitor application, as proton can easily permeate through the bulk of the electrode materials where the whole electrode can be utilized for energy storage [40].…”
Section: Introductionsupporting
confidence: 90%
“…In this study, it was revealed that the use of ITO as the substrate led to the formation of amorphous phase, which agreed well with the findings of other workers [36,37]. However, the use of copper substrate for example, can yield crystalline phase of the deposits [38,39]. The amorphous phase is suitable for super capacitor application, as proton can easily permeate through the bulk of the electrode materials where the whole electrode can be utilized for energy storage [40].…”
Section: Introductionsupporting
confidence: 90%
“…14 We report here that the concentration gradient in 5-500 nm thin NiFe films is related to the dynamics of the surface roughening and changes in current efficiency during the early stages of deposition.…”
mentioning
confidence: 80%
“…13,14 For the application of thin magnetic film with thickness <200 nm, the composition gradient would be detrimental in controlling of magnetic properties. It had been shown earlier 9,10 that the composition in NiFe films is stabilized more quickly in the case of pulse electrodeposition compared to galvanostatic electrodeposition.…”
mentioning
confidence: 99%
“…Historically, the spontaneous variation of the alloy composition during d.c. plating was detected as the change of the average composition as a function of the thickness [10][11][12][13][14]. Although this procedure is well indicative of a composition change, it is an integral method, which also means that its sensitivity to either local effects or subtle changes is very little.…”
Section: Introductionmentioning
confidence: 99%